2023
DOI: 10.1186/s40634-023-00622-y
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of inferior pole fractures of the patella: a systematic review

Abstract: Purpose This study aimed to comprehensively review the existing evidence concerning surgical treatment of inferior pole fractures of the patella and to report the outcomes and complications of different fixation techniques. Method This systematic review was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Searches of PubMed, Scopus, and Web of Science were conducted in March 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…The combined distal pole fractures were easily to overlooked in the traditional x-ray examination and seldom to manage in clinical practice, which may affect the function prognosis and lead to fixation failure. Non-rigid internal fixation of the inferior pole fracture would disrupt the extensor mechanism, which results in considerable functional disability (29). A research revealed that the anchor and Krackow-"8" Suture for the fixation of distal pole fracture was an effective operation method and better surgical outcome (30).…”
Section: Discussionmentioning
confidence: 99%
“…The combined distal pole fractures were easily to overlooked in the traditional x-ray examination and seldom to manage in clinical practice, which may affect the function prognosis and lead to fixation failure. Non-rigid internal fixation of the inferior pole fracture would disrupt the extensor mechanism, which results in considerable functional disability (29). A research revealed that the anchor and Krackow-"8" Suture for the fixation of distal pole fracture was an effective operation method and better surgical outcome (30).…”
Section: Discussionmentioning
confidence: 99%